At the interface of sensory and motor dysfunctions and Alzheimer's disease. Issue 1 (8th July 2014) - Albers, Mark W.; Gilmore, Grover C.; Kaye, Jeffrey; Murphy, Claire; Wingfield, Arthur; Bennett, David A.; Boxer, Adam L.; Buchman, Aron S.; Cruickshanks, Karen J.; Devanand, Davangere P.; Duffy, Charles J.; Gall, Christine M.; et al.
Abstract: Recent evidence indicates that sensory and motor changes may precede the cognitive symptoms of Alzheimer's disease (AD) by several years and may signify increased risk of developing AD. Traditionally, sensory and motor dysfunctions in aging and AD have been studied separately. To ascertain the evidence supporting the relationship between age‐related changes in sensory and motor systems and the development of AD and to facilitate communication between several disciplines, the National Institute on Aging held an exploratory workshop titled "Sensory and Motor Dysfunctions in Aging and AD." The scientific sessions of the workshop focused on age‐related and neuropathologic changes in the olfactory, visual, auditory, and motor systems, followed by extensive discussion and hypothesis generation related to the possible links among sensory, cognitive, and motor domains in aging and AD. Based on the data presented and discussed at this workshop, it is clear that sensory and motor regions of the central nervous system are affected by AD pathology and that interventions targeting amelioration of sensory‐motor deficits in AD may enhance patient function as AD progresses.